The use of unmanned aerial vehicles (drones) to determine the shoreline of natural watercourses - Wilkowski Wojciech; Lisowski Marcin; Wyszyński Marek; Wierzbicki Damian (Journal of Water and Land Development, 2017)
The aim of the paper was to study the possibility of using unmanned aerial vehicles (drones) to determine the shoreline of natural watercourses.